Study of Generator Set Overload Protection System in Power Generation Units - Bambang Winardi; Agung Nugroho (Yayasan Ghalih Pelopor Pendidikan (Ghalih Foundation), 2022)
The need for electrical energy in an industry is very important for the production process to run. To meet the demand for electrical energy, one can use a power source from PLN or use an independent power source by establishing a power plant. The Power Plant Unit is a unit that functions to provide electrical energy needs for the production process at PPSDM Migas. Electricity generation in the Power Plant Unit, namely Pembangkit Listrik Tenaga Diesel (PLTD) using a generator set that uses diesel fuel. A generator set or generator is a generator that has been equipped with a prime mover. Gensets that work continuously are certainly inseparable from disturbances such as the occurrence of overloads. Overload disturbance occurs because the amount of load power supplied by the generator is greater than the capacity of the working generator. Air Circuit Breaker (ACB) is one of the protective equipment used to protect generator sets. Inside the ACB there is Over Current Trip equipment that will work if there is an overload on the generator. The capacity of the generator used is 1000kVA/400V with a nominal generator current of 1443.38 A. Under normal load conditions, the installed load power is 354.5 kW with a load current of 639.6 A. Then at peak load conditions, the installed load power is 510,3 kW with a load current of 920.7 A. In both conditions, the load current does not exceed the nominal current of the generator so Over Current Trip does not instruct ACB to trip. However, it is possible for overload disturbances to occur if there is no coordination between the operator at the power plant and the load operator (refinery & utilities) so that the operation of the load is not controlled.